GABA‐containing compound gammapyrone protects against brain impairments in Alzheimer's disease model male rats and prevents mitochondrial dysfunction in cell culture. Issue 6 (11th February 2019) - Pilipenko, Vladimirs; Narbute, Karina; Amara, Ines; Trovato, Angela; Scuto, Maria; Pupure, Jolanta; Jansone, Baiba; Poikans, Janis; Bisenieks, Egils; Klusa, Vija; Calabrese, Vittorio
Abstract: Neuroinflammation, oxidative stress, decreased glucose/energy metabolism, and disrupted neurotransmission are changes that occur early in sporadic Alzheimer's disease (AD), manifesting as mild cognitive impairment. Recently, the imbalanced function of the gamma‐aminobutyric acid (GABA) system was identified as a critical factor in AD progression. Thus, maintaining balance among neurotransmitter systems, particularly the GABA system, can be considered a beneficial strategy to slow AD progression. The present study investigated the effects of the compound gammapyrone, a molecule containing three GABA moieties: "free" moiety attached to the position 4 of the 1, 4‐dihydropyridine (DHP) ring, and two "crypto" moieties as part of the DHP scaffold. The "free" and "crypto" GABA moieties are linked by a peptide bond (–CONH–), resulting in a peptide‐mimicking structure. In a nontransgenic male rat AD model generated by intracerebroventricular (icv) streptozocin (STZ) administration, gammapyrone (0.1 and 0.5 mg/kg ip) mitigated the impairment of spatial learning and memory, prevented astroglial and microglial neuroinflammation, and normalized acetylcholine breakdown and GABA biosynthesis. In PC12 cells, gammapyrone protected against oxidative stress, mitochondrial dysfunction and apoptosis caused by the mitochondrial toxin di‐2‐ethylhexyl phthalate (DEHP). Gammapyrone did not bind to GABA‐A and GABA‐B receptors in vitro; therefore, we cannot attribute its neuroprotective action to a specific interaction with GABA receptors. Nevertheless, we suggest that the peptide‐like regulatory mechanisms of gammapyrone or its allosteric modulatory properties are essential for the observed effects. Since, the icv STZ model resembles the early stages of AD, gammapyrone, and/or its congeners could be useful in the design of anti‐dementia drugs. Abstract : GABA‐containing compound gammapyrone was studied in Alzheimer's disease model male rats. It attenuated spatial learning/memory impairments, prevented astroglial/microglial activation, normalized GABA synthesizing enzyme density and reduced acetylcholine cleaving enzyme density.